Sleep Disturbances in Patients With Alzheimer Disease and Dementia With Lewy Bodies - Emek Savaş, Derya Durusu; Balkan, Barış; Yener, Görsev (Journal Neurological Sciences, Ege Univ Hosp. Fac Med, Dept Neurosurgery, Bornova-Izmir, Tr35100, Turkey, 2014)
Objective: We compared subjective sleep quality, sleep disturbances and excessive daytime sleepiness (EDS) in non-demented elderly, patients with Alzheimer disease (AD) and dementia with Lewy bodies (DLB). We investigated whether sleep dysfunction and EDS are associated with the severity of dementia. Methods: The sleep profiles of 85 non-demented elderly, 84 patients with AD and 31 with DLB were assessed using two questionnaires, Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS). In order to evaluate the severity of dementia in patients with AD and DLB and to determine the non-demented elderly, Mini Mental State Examination (MMSE) and Clinical Dementia Rating Scale (CDR) were used. Results: AD and DLB patients had worse sleep quality and more sleep disturbances when compared to non-demented elderly. EDS was also more frequent in AD and DLB patients than in non-demented elderly. There was no significant difference between AD and DLB patients in terms of sleep quality or EDS. Having bad dreams -single item on PSQI- was more frequent in DLB patients when compared with AD and non-demented elderly. Sleep dysfunction and EDS were not associated with the severity of dementia. Conclusion: Both patient groups had extensive sleep problems. Poor sleep quality and EDS were greater in AD and DLB patients compared with controls.
Keywords: Alzheimer Disease; Dementia with Lewy Bodies; Sleep; Sleep Disturbances; Sleep Disorders; Quality of Sleep; Excessive Daytime Sleepiness; Circadian-Rhythm Disturbances; Nursing-Home Patients; Behavior Disorder; Parkinsons-Disease; Daytime Sleepiness; Older-Adults; Scale; Epidemiology